(untitled) - Gallo, Tina (New York, 2020)
When the local library tries to cancel story time because the babies are too loud, its up to Boss Baby and this trusty team to save the day!
1
Keywords: Noise; Fiction; Fiction; Babies; Fiction; Libraries; Infants; Noise; Juvenile fiction; Juvenile fiction; Libraries; Juvenile fiction; Readers (Primary)